Porphyromonas gingivalis-induced periodontitis could contribute to cognitive impairment in Sprague–Dawley rats via the P38 MAPK signaling pathway - Jin, Ru; Ning, Xiaoqiao; Liu, Xiang; Zhao, Yueyang; Ye, Guo (Frontiers in Cellular Neuroscience, 2023)
Over recent years, the relationship between periodontitis and neurodegenerative diseases has received increasing attention. Cognitive impairment, which is considered as a precursor to neurodegenerative diseases, has also been extensively studied. However, periodontitis models have not been directly constructed in various studies to probe into the relationship between periodontitis and cognitive impairment. Thus, in this study, a periodontitis model was established by ligating the first molars of Sprague‒Dawley (SD) rats with silk thread and injecting Porphyromonas gingivalis or Porphyromonas gingivalis plus the P38MAPK inhibitor SB203580 simultaneously. The research objective was to investigate the relationship between periodontitis and cognitive impairment, aiming at exploring the role of the P38MAPK signaling pathway in this process. The results showed that silk ligature-induced periodontitis plus injection of P. gingivalis into subgingival tissue could be responsible for memory and cognitive impairment. In addition, transcriptome sequencing results suggested the neurodegenerative diseases in the P. gingivalis group. We found high levels of inflammatory factors and the upregulated expression of specific pathological markers of the neurodegenerative diseases, along with the P38MAPK pathway activation. In conclusion, the findings indicate that the topical application of Porphyromonas gingivalis increases the inflammatory burden in the peripheral and central nervous systems (CNS) and that impaired learning and memory in SD rats can be attributed to the neuroinflammation induced by the activation of P38MAPK. Therefore, P38MAPK may serve as a linking pathway between periodontitis and cognitive impairment.